Seven-year microbiological profile and antibiotic sensitivity pattern of burn wound infections in a tertiary care hospital in New Delhi - Vikas Singh; Naveen Grover; Kundan Tandel; Salil Jena (Wolters Kluwer Medknow Publications, 2022)
Introduction: Burn patients are vulnerable for opportunistic colonization by organisms of endogenous and exogenous origin. Hence, it is necessary to evaluate the flora obtained from wounds of burn patients to determine the most effective treatment. The aim of this study was to determine the incidence of various bacteria isolated from burn patients and to determine their antimicrobial susceptibility and resistance pattern spanning 7 years. Materials and Methods: The retrospective study included all the culture reports obtained over a period of 7 years (2012-2018). Results: Out of the total 1474 positive samples analyzed, the most common sample reported was pus (n = 816), followed by blood culture (n = 314), tissue (n = 188), and urine (n = 156). The most common organism cultured was Pseudomonas aeruginosa (n = 377), followed by Klebsiella pneumoniae (n = 309). Other commonly isolated organisms were Acinetobacter baumannii (n = 206), Escherichia coli (n = 89), coagulase-negative staphylococci (n = 88), Proteus mirabilis (n = 55), Burkholderia cepacia (n = 54), Staphylococcus aureus (n = 42), Candida spp. (n = 39), and Enterococci spp. (n = 36). Pseudomonas was seen to be sensitive to only colistin with resistance to all other major antibiotic classes. Klebsiella was sensitive to colistin, tigecycline, and cefoperazone/sulbactam. A. baumannii was observed to be sensitive only to colistin and tigecycline by the end of 2018 and E. coli was sensitive to amikacin, colistin, meropenem, and tigecycline. Conclusion: Antibiotic resistance is rampant, rapidly progressing and devouring down all the antibiotic classes one after other. The high antimicrobial resistance may be ascribed to the inappropriate use of broad-spectrum antibiotics and lack of a definite antibiotic policy in hospitals. Treating surgeons should frequently evaluate the burn patient and run regular tests to localize the most common organisms causing the infections with their antibiotic sensitivity profiles.